Geometric SMOTE a geometrically enhanced drop-in replacement for SMOTE - Douzas, Georgios (2019)
Douzas, G., & Bacao, F. (2019). Geometric SMOTE a geometrically enhanced drop-in replacement for SMOTE. Information Sciences, 501, 118-135. https://doi.org/10.1016/j.ins.2019.06.007